Pengaruh Religiositas Dan Pengetahuan Halal Sepatu Berbahan Dasar Kulit Babi Terhadap Keputusan Pembelian: (Studi Pada Pengguna New Balance) - Astuti, Farrah Diva; Artadita, Sherly (eProceedings of Management, 2024)
In modern times, one of the fastest growing industries is the shoe industry. New Balance ranks third in the TOP BrandIndex 2023. However, there are differences in understanding between fellow users of New Balance shoes on socialmedia about the use of pigskin-based ingredients in New Balance shoes. Therefore, this study aims to determine andanalyze the effect of religiosity and halal knowledge of pork skin-based shoes on purchasing decisions of New Balanceshoe users. The population used in this study are all Muslim consumers and have purchased New Balance shoes. Datacollection was carried out using a non-probability method with purposive sampling technique and collected as manyas 100 respondents in filling out the questionnaire. The results of this research, there is a positive and significantinfluence between the religiosity of pigskin-based shoes on the purchasing decisions of New balance shoe users withtcount 2.541 and there is a significant and positive influence between halal knowledge of pigskin-based shoes on thepurchasing decisions of New balance shoe users with tcount 5.308. Then religiosity and halal knowledge of pork skinbased shoes simultaneously have a significant effect on the purchasing decisions of New balance shoe users withfcount 44.683. The contribution of the influence of the independent variables of religiosity and halal knowledge onthe dependent variable of purchasing decisions is 47.8% and the remaining 52.2% is influenced by other variablesnot examined in this research. Keywords-religiosity, halal knowledge, purchase decisions